Spiro [indoline-3,4′-pyrano[2,3-c]pyrazole] Derivatives as Novel Class of Green Corrosion Inhibitors for Mild Steel in Hydrochloric Acid Medium: Theoretical and Experimental Approach - Gupta N.K.; Haque J.; Salghi R.; Lgaz H.; Mukherjee A.K.; Quraishi M.A. (My University, 2025)
Present study deals with synthesis and inhibition effect of two new spiro[indoline-3,4′-pyrano[2,3-c]pyrazole] derivatives, namely 6′-amino-3′-methyl-2-oxo-1′H-spiro[indoline-3,4′-pyrano[2,3-c]pyrazole]-5′-carbonitrile (SIPP-1) and 6′-amino-3′-methyl-2-oxo-1′-phenyl-1′H-spiro[indoline-3,4′-pyrano[2,3-c]pyrazole]-5′-carbonitrile (SIPP-2) on mild steel corrosion in 1 M hydrochloric acid solution using experimental and theoretical techniques. These inhibitors were synthesized using the concept of Green Chemistry by one-step multicomponent reactions (MCRs) involving ultrasound as an energy source. The gravimetric results showed that inhibition efficiency of the studied compounds increases with the concentration and maximum efficiency of 95.65 (SIPP-1) and 96.95 (SIPP-2) was achieved at an optimum concentration of 200 ppm. Potentiodynamic polarization study reveals that the studied compounds act as a mixed type but predominantly cathodic-type inhibitor. Adsorption of the tested inhibitors on the metallic surface obeyed the Langmuir adsorption isotherm. The adsorption of these compounds on the metallic surface was supported by scanning electron microscopy and atomic force microscopic methods. A good correlation between theoretical and experimental results was obtained. The orientation inhibitor molecules on the metallic surface and interaction energies of these molecules were obtained using molecular dynamic simulation study. Both experimental and theoretical studies suggest the better inhibition performance of SIPP-2 and well corroborated each other. © 2018, Springer International Publishing AG, part of Springer Nature.